Asuhan Kebidanan Komprehensif pada Ny. H di Rumah Sakit Ibu dan Anak Masyita - Putri Dwi Aidilia; Nurhayati Nurhayati; Nurlina Akbar (Window of Midwifery Journal, 2026)
Maternal Globally and nationally, maternal mortality rate and infant mortality rate remain major public health concerns. The Sustainable Development Goals (SDGs) 2030 target is to reduce MMR to below 70 per 100,000 live births and IMR to below 12 per 1,000 live births. The periods of pregnancy, childbirth, postpartum, newborn care, and family planning services are critical stages with high risk for morbidity and mortality. Therefore, comprehensive and continuous midwifery care is essential. This study aimed to implement comprehensive midwifery care for Mrs. “H” at RSIA Masyita Makassar, covering pregnancy, labor, postpartum, newborn care, and family planning services. The care was provided using Varney’s 7-step midwifery management process and documented using the SOAP format. Data were collected through interviews, physical examinations, observation, supporting examinations, and documentation studies. The results showed that Mrs. “H”, G5P4A0 with a gestational age of 38 weeks and 6 days, attended seven antenatal visits without any complaints or danger signs. The delivery occurred normally, and the baby was born spontaneously in good condition. The postpartum period was physiological, with three postnatal visits. At the end of the care, family planning counseling was provided, and the mother chose the implant contraceptive method. This care is expected to enhance maternal understanding of early complication detection and assist students in developing clinical skills in providing comprehensive midwifery services.